#TITLE_ALTERNATIVE# - FAUZAN AZMI LUBIS (NIM : 15109053) ; Pembimbing I : Dr. Ir. Eka Djunarsjah, MT. ; Pembimbing II
Bathymetric survey is a measurement process of the seabed depth which can be utilized for various purposes, one of them is to the determination the route of the underwater pipeline installation. The Information of underwater pipeline route is needed for the underwater pipeline installation as a utilities of effective and efficient transportation for distribution of oil and gas.In this bathymetric survey, the collected data including the depth data at every positions points in Tanjung Priok and tide observation data in Damar Islands. Data processing starts from processing of the depth data, which referenced to tide data of Damar Islands. The result of this process is bathymetric chart or depth contours. Then the design of underwater pipeline route is made from bathymetric chart, which are obtained from depth contours and slope data. The design of pipeline route is manually made in ArcGIS through some combination of pipeline route. The pipeline route must be fulfill three criterias of the underwater pipeline route selection, namely: pipeline route which will be determined must be safe; make the process of pipeline installation easier; and have the shorthest route. The best design of underwater pipeline route is chosen from some combination of pipeline route which have fulfill of those criterias above. Based on the results of data processing, the plan of pipeline route which have fulfill the criteria of underwater pipeline route selection which can be seen from bathymetric and slope data. The best plan of underwater pipeline route in this survey is the pipeline route which closed to the middle of corridor survey, with the shortest route is 23.899 km.